Influence of weeding regime on productivity of aerobic rice genotypes - Taketsaba, Aliyu Isah; Juraimi, Abdul Shukor; Yusop, Mohd Rafii; Othman, Radziah; Singh, Ajit (Faculty of Agriculture, Universiti Putra Malaysia, 2018)
Aerobic Rice Production Systems (ARPS), an innovative production method in which rice is grown under nonpuddled, nonflooded and nonsaturated soil environments are subject to considerable greater weed stress. Two field experiments were conducted at Field 10, Universiti Putra Malaysia (UPM), (latitude 30 02’N; longitude 1010 42’ E and on the altitude of 31 m above sea level) Selangor, Malaysia during the off-season (May to September 2015) and main season (September to December 2015) to investigate the effect of weeding regime on weed species composition and yielding potential of some aerobic rice genotypes. It consisted of two (2) weeding regimes (weed-free and weedy check) and three aerobic rice genotypes (MRIA1, MR219-4 and MR219-9). Results revealed that at harvest a total of 20 weed species were identified in the two seasons. The weed flora for the two seasons dominantly consisted of 12 broadleaves (49.28%), followed by 6 kinds of grass (30.31%) and by 2 sedges (20.41%). The most dominant weeds in the two seasons were Cyperus iria L., Ageratum houstonianum Mill., Cleome rutidosperma DC., and Digitaria horizontalis Willd. that constituted more than 53.33% of the sum dominance-ratio. MRIA1 recorded the utmost (72.35 no. m-2 and 358.27 g m-2) weed density and dry weight and the lowest (48.81 no. m-2 and 168.89 g m-2) weed density and dry weight was recorded in MR219-9. In comparison with other genotypes, MRIA1 by means of having elevated plant height, limited tillers, and shorter growth duration vied unwell with weeds than other genotypes (MR219-4 and MR219-9) with undersized plants, numerous tillers and extended growth period. Lesser weed dry weight, greater weed competitive index and corresponding yield loss recorded in MR219-9 disclosed its superior capability of weed conquest and tolerance. The results concluded that growing MR219-9 genotype in aerobic condition can improve weed management in rice production.